Speckle-free near-infrared imaging using a Nd3+ random laser. (19th September 2017) - Barredo-Zuriarrain, M; Iparraguirre, I; Fernández, J; Azkargorta, J; Balda, R
Abstract: Single shot infrared images of different patterns obtained, both by reflection and transmission, with a near infrared random laser source and a narrowband laser are analyzed under similar experimental conditions. The Nd-based crystal powder random laser provides speckle-free transmission and reflection infrared images with higher values of contrast to noise ratio than those obtained with the narrowband laser. These results open up new possibilities to enhance the field of high resolution imaging for optoelectronic and biomedical applications.